Once rosas - Ramírez, Esteban (Filmmaker); Sánchez, Mónica, 1970-; Gómez, Fabricio (Cinetel, 2000)
Rafa, a young photographer, is fascinated by Mariana, a mysterious beauty that he portrays by chance while working on the street. This casual encounter will impel him to the search of the woman who lives both in his dreams and in his images, guided by the illusion of love at first sight.--